Magma evolution and open-system processes at Shiveluch Volcano: Insights from phenocryst zoning - Humphreys, M; Blundy, J; Sparks, R (2006)
Phenocryst zoning patterns are used to identify open-system magmatic processes in the products of the 2001 eruption of Shiveluch Volcano, Kamchatka. The lavas and pumices studied are hornblende-plagioclase andesites with average pre-eruptive temperatures of ∼840°C and fO2 of 1.5-2.1 log units above nickel-nickel oxide (NNO). Plagioclase zoning includes oscillatory and patchy zonation and sieve textures. Hornblendes are commonly unzoned, but some show simple, multiple or patchy zoning. Apatite microphenocrysts display normal and reverse zoning of sulphur. The textural similarity of patchy hornblende and plagioclase, together with Ba-Sr systematics in patchy plagioclase, indicate that the cores of these crystals were derived from cumulate material. Plagioclase-liquid equilibria suggest that the patchy texture develops by resorption during H2O-undersaturated decompression. When H2O-saturated crystallization recommences at lower pressure, reduced pH2O results in lower XAn in plagioclase, causing more Al-rich hornblende to crystallize. Plagioclase cores with diffuse oscillatory zoning, and unzoned hornblende crystals, probably represent a population of crystals resident in the magma chamber for long periods of time. In contrast, oscillatory zoning in the rims of plagioclase phenocrysts may reflect eruption dynamics during decompression crystallization. Increasing Fe/Al in oscillatory zoned rims suggests oxidation as a result of degassing of H2O during decompression. A general lack of textural overlap between phenocryst types suggests that different phenocryst populations were spatially or temporally isolated during crystallization. We present evidence that the host andesite has mixed with both more felsic and more mafic magmas. Olivine and orthopyroxene xenocrysts with reaction or overgrowth rims and strong normal zoning indicate mixing with basalt. Sieve-textured plagioclase resulted from mixing of a more felsic magma with the host andesite. The mineralogy and mineral compositions of a mafic andesite enclave are identical to those of the host magma, which implies efficient thermal quenching, and thus small volumes of intruding magma. Mixing of this magma with the host andesite results in phenocryst zoning because of differences in dissolved volatile contents. We suggest that small magma pulses differentiated at depth and ascended intermittently into the growing magma chamber, producing incremental variations in whole-rock compositions. © 2006 Oxford University Press.